Enhanced Biosorption of Nickel Ions on Immobilized Surface-Engineered Yeast Using Nickel-Binding Peptides - Li, Hua; Dong, Wei; Liu, Yong; Zhang, Haiyan; Wang, Gang (Frontiers in Microbiology, 2019)
Three nickel-binding peptides were screened from a phage peptide library and displayed separately or in combination with surface-engineered Saccharomyces cerevisiae EBY100. The sorption of nickel ions on the surface of yeast cells increased with the increasing number of nickel Ni(II)-binding peptides displayed. The combined expression of the three peptides by EBY100/pYD1-N123 demonstrated the highest sorption of Ni(II) (2.603 ± 0.004 g g−1, dry weight) and an enhanced sorption capacity of 60.15%, compared to S. cerevisiae EBY100. An orthogonal test for yeast immobilization was designed. A maximum sorption capability of 68.62% was observed for a treatment at 25°C with 2.0% calcium chloride and 3.0% sodium alginate.